2019
DOI: 10.1002/iub.2103
|View full text |Cite
|
Sign up to set email alerts
|

Key candidate genes of STAT1 and CXCL10 in melanoma identified by integrated bioinformatical analysis

Abstract: The underlying mechanisms and gene signatures of melanoma are unknown. In this study, three expression profile data sets (GSE65568, GSE100050, GSE114445) were integrated to identify candidate genes explaining the pathways and functions of melanoma. Expression data sets including 24 melanoma tumours and 13 normal skin samples were merged and analysed in detail. The three GSE profiles shared 431 differentially expressed genes (DEGs), including 227 upregulated genes, 200 downregulated genes and 4 differentially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…39 In melanoma, CXCL10 was reported as a key candidate gene by integrated bioinformatics analysis. 40 The above research results indicated that the IRGs in our signature may be involved in the occurrence and development of SKCM.…”
Section: Discussionmentioning
confidence: 64%
“…39 In melanoma, CXCL10 was reported as a key candidate gene by integrated bioinformatics analysis. 40 The above research results indicated that the IRGs in our signature may be involved in the occurrence and development of SKCM.…”
Section: Discussionmentioning
confidence: 64%
“…CXCL10, as a "key driver chemokine" as well as an effective target for treating autoimmune diseases [33], has been a target for novel cancer therapy in immune activation functions [34]. In melanoma, CXCL10 was reported as a key candidate gene by integrated bioinformatics analysis [35]. The above research results indicated that the IRGs in our signature may be involved in the occurrence and development of SKCM.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, STAT1 and CXCL10 affect bone destruction through the M1 polarization of macrophages [ 22 ]. CXCL10 and STAT1 have also been suggested as key candidate genes for understanding the molecular mechanism of melanoma [ 42 ]. STAT1 is known to be activated by IFN-γ.…”
Section: Discussionmentioning
confidence: 99%